Design of a nanocomposite substrate inducing adult stem cell assembly and progression toward an Epiblast-like or Primitive Endoderm-like phenotype via mechanotransduction. (November 2017) - Morena, Francesco; Armentano, Ilaria; Montanucci, Pia; Argentati, Chiara; Fortunati, Elena; Montesano, Simona; Bicchi, Ilaria; Pescara, Teresa; Pennoni, Ilaria; Mattioli, Samantha; Torre, Luigi; Latterini, Loredana; et al.
Abstract: This work shows that the active interaction between human umbilical cord matrix stem cells and Poly (l -lactide)acid (PLLA) and PLLA/Multi Walled Carbon Nanotubes (MWCNTs) nanocomposite films results in the stem cell assembly as a spheroid conformation and affects the stem cell fate transition. We demonstrated that spheroids directly respond to a tunable surface and the bulk properties (electric, dielectric and thermal) of plain and nanocomposite PLLA films by triggering a mechanotransduction axis. This stepwise process starts from tethering of the cells' focal adhesion proteins to the surface, together with the adherens junctions between cells. Both complexes transmit traction forces to F-Actin stress fibres that link Filamin-A and Myosin-IIA proteins, generating a biological scaffold, with increased stiffening conformation from PLLA to PLLA/MWCNTs, and enable the nucleoskeleton proteins to boost chromatin reprogramming processes. Herein, the opposite expression of NANOG and GATA6 transcription factors, together with other lineage specification related proteins, steer spheroids toward an Epiblast-like or Primitive Endoderm-like lineage commitment, depending on the absence or presence of 1 wt% MWCNTs, respectively. This work represents a pioneering effort to create a stem cell/material interface that can model the stem cell fate transition under growth culture conditions. Graphical abstract: Cartoon shows that the hUCMSCs-PLLA polymer and -PLLA/MWCNTs nanocomposite interface induce the self-organization of stem cells in spheroids and in turn drives a tweaking mechanotransduction axis that steers stem cells toward spheroids with Epiblast-like phenotype on PLLA polymer and spheroids with Primitive-Endoderm-like phenotype on 1MWCNTs nanocomposites.